Comparative Analysis of Personal Trainers’ Job Roles in Latecomer Growth Cities Using DACUM (Developing A Curriculum): A Comparative Study of Zhengzhou and Seoul - Junyang Yan(Junyang Yan), Jisang Yu(Jisang Yu), Kyongken Choi(Kyongken Choi), Jinho Yoo(Jinho Yoo) (The Asian journal of kinesiology, 2025)
OBJECTIVES This study aimed to systematically analyze the job roles of personal trainers in Latecomer Growth Cities using the DACUM method, focusing on identifying core Duties and Tasks, and comparing CVR(Content Validity Ratio), convergence, and consensus between Zhengzhou and Seoul. METHODS A structured DACUM-based job analysis was conducted, involving 130 personal trainers in Zhengzhou. Surveys assessed 65 Tasks across nine Duties. Quantitative metrics (CVR, convergence, consensus) were applied, with comparativeanalysis against Seoul’s data. RESULTS High CVR and consensus were observed in core Duties (exercise program design, instruction, safety management) across both cities, indicating universal standards. Significant disparities emerged in extended roles (client communication, personal branding), with Zhengzhou showing lower procedural compliance (e.g., pre-assessment documentation) and Seoul demonstrating superior system maturity. Zhengzhou’s Tasks A-2 (PAR-Q use) and A-3 (informed consent) failed validation thresholds (CVR <0.42), while Seoul maintained higher execution rates. CONCLUSIONS DACUM effectively highlights regional differences in job role perceptions. Personal trainers’ roles must expand beyond foundational skills to include communication and digital competencies. Tailored training programs and standardized protocols are recommended for Latecomer Growth Cities, while mature systems should prioritize role redefinition and continuous education. KCI Citation Count: 0